The return of the haze: an analysis of Singapore Government’s behavior before and after the 2013 haze attack - Lee, Pei May; Masri, Mohd Syazani (Naresuan University, 2017)
This paper compares and analyses Singapore government’s commitments towards the past haze phenomenon with the haze attack on 2013. In the past, Singapore seemed to be quite willing to tolerate hazy skies and choking smog caused by the haze; but the haze in June 2013 oversees significant change in Singapore’s behavior from being half-hearted to fully commit in resolving the haze issue. There are many approaches to argue the change in government position, but this article argues that the main reason behind the change in Singapore’s behavior is due to the persistent competition between various individuals and groups. This changing dynamics is well-captured by Liberalism school of thought. Though many scholars had looked into the haze issue in Southeast Asia, but only a limited number of studies have focused on states’ behaviour. This paper contributes to the body of knowledge in the studies of Southeast Asia politics as well as to the haze issue, which is the most pertinent issue in Southeast Asia region. This paper does not analyse how this incidence can induce social movement since haze is a periodical phenomenon. Moreover, the nature of this paper does not intend to include policy recommendation to the government because the theoretical framework employed focus more on explaining the interactions of different groups in the society and how it influences state’s behavior.